Safety helmet with air quality sensor / Nurhanis Hanissa Junaidi and Anas Zafirol Abdullah Halim - Junaidi, Nurhanis Hanissa; Abdullah Halim, Anas Zafirol (2023)
Outdoor air pollution has emerged as a global public health concern, affecting millions of individuals worldwide. Exposure to high levels of air pollutants, including volatile organic compounds (VOCs) and particulate matter (PM), can lead to severe health consequences, even causing instantaneous death. Among the affected, frontline construction workers and managers face additional risks due to exposure to construction dust. To address this issue, the present research aims to develop an innovative product, i.e., A Safety Helmet with Air Quality Sensor, specifically designed for construction industry workers. The research objectives include conceptualising design ideas for the Safety Helmet with Air Quality Sensor, assembling a prototype based on the improvised design, demonstrating its performance, and exploring its marketability potential. The visualisation of the innovation idea was achieved through a simulation using SolidWorks software to facilitate in understanding the concept and design.